Karakteristik Pelaksanaan Pembinaan Santri di Asrama Pondok Pesantren - Adam Saputra (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of the implementation of fostering students in the hostel reveals the characteristics of the coaches of students through a process of approach, education, and habituation that is applied in a series of activities both inside and outside the hostel. This research is field research with a qualitative descriptive approach with natural characteristics as a direct data source. Data collection through observation techniques, interviews, and documentation. Data analysis techniques with inductive and deductive methods. The issues discussed include various characteristics of the implementation of coaching students in dormitories with various actuating, directing, leading, coordinating, and motivating elements. The results of this study indicate that Actuating characteristics have been applied properly and consistently with a good approach to fostering students in the dormitory. Characteristics of Directing by giving directions and providing various information related to what hostel activities will be carried out every day. Leading characteristics provide an example of a leader and the best role model for students in carrying out a series of activities for students in the dormitory. Coordinating Characteristics There is a good cooperative relationship or teamwork between Santri coaches, dormitory administrators, and OSPI administrators intensely in coordinating coaching in the dormitory to achieve goals effectively and efficiently. Motivating characteristics provide various motivations, and enthusiasm for learning and provide reasons why it must be implemented. This implementation has different characteristics such as the existence of an iqob system (educational punishment), role models, and a system of learning contracts, activity contracts, and contracts in the hostel. These efforts can provide solutions to foster properly according to the goals to be achieved.